(untitled) (Ameghiniana, 2013)
This paper has been divided in three parts: (1) geological consíderations about the Arroyo Chasicó Formation (Lower Pliocene), from the SW of Buenos AIres Province, with a .brief summary a out th.e. lith?logical char cteristics, geographical distríbutíon, thickness, fossíl mammals and íts posítíon m a correlation chart of all the mammal. - bearling formations of Buenos Aires Province and the rest of the country; (2) systematícs and description of the Toxodontidae (Notoungulata) found in the outcrops of the Arroyo Chasicó; and (3) some considerations on the evidences upon which the plio - pleistocene Toxodontidae systematic has been based, including their possible phyrogenetic relationships.